Parasocial Relationship dengan Selebritas (Studi Kualitatif pada Praktik Penggunaan Fandom Applications) - Lidwina Mutia Sadasri (Jurnal Studi Pemuda, 2021)
Fan fanaticism towards their idol celebrity nowadays is easier to find. Compared to the previous period when interacting with idols could only be mediated by sending letters or press conferences, the presence of new media now allows fans to interact with their idols and connect through online social media, which can lead to the essence of parasocial relationships. One of the platforms that facilitates the relationship between fans and their idols is the fandom application, two of which are popular, Bubble and WeVerse. In this research, the goal is to analyze fans’ experience in using the fandom application using the concept of consumption of commercial products. Through reception analysis and in-depth interview techniques with informants, this study seeks to map the consumption practices of NCT and BTS fans using concepts that are dissected into consump- tion, projection, collection, reflection, and construction. The research results show that the platform further strengthens the relationship between fans and idols, especially the pandemic conditions that give fans more free time to access content from idols. Although not all of them took the reflection and construction stages seriously, their efforts almost covered all consumption activities due to the informant’s background and the intensity of the fans-idol relationship.